The Effect of Principal's Transformational Leadership and Teacher Work Commitment on Instructional Performance Outcomes in Public Elementary Schools - Gusra Farnita; Nurhizrah Gistituati; Nellitawati Nellitawati; Ahmad Sabandi; Erwin Pri Utomo (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This study aimed to analyze the influence of principals’ transformational leadership and teacher work commitment on instructional performance outcomes in public elementary schools in Padang Pariaman Regency, Indonesia. This study employed a quantitative explanatory research design. The sample consisted of 182 teachers selected through cluster multistage stratified random sampling. Data were collected using a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics, simple regression, and multiple regression analysis. The findings showed that principals’ transformational leadership had a positive and significant effect on teachers’ instructional performance outcomes. In contrast, teacher work commitment did not have a significant partial effect, although teachers generally demonstrated a good level of commitment. Simultaneously, transformational leadership and work commitment had a significant effect on instructional performance outcomes; however, their combined contribution was relatively small, explaining only 4.0% of the variance. Transformational leadership emerged as the dominant predictor in the model. The study concludes that improving instructional performance outcomes requires strengthening principals’ transformational leadership, particularly intellectual stimulation and individualized consideration, while also supporting teachers through professional development, adequate resources, and conducive school conditions.